2009
DOI: 10.1080/10615800802272244
|View full text |Cite
|
Sign up to set email alerts
|

Traits, states, and attentional gates: Temperament and threat relevance as predictors of attentional bias to social threat

Abstract: This study investigated the influence of situational and dispositional factors on attentional biases toward social threat, and the impact of these attentional biases on distress in a sample of adolescents. Results suggest greater biases for personally-relevant threat cues, as individuals reporting high social stress were vigilant to subliminal social threat cues, but not physical threat cues, and those reporting low social stress showed no attentional biases. Individual differences in fearful temperament and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…This builds on the work of Salemink and Wiers (2012) by showing that a within-participants experimental manipulation of executive control capacity (WM load) moderates trait anxiety's effects on interpretive bias, and supports the hypothesis that latent emotion-related biases influence cognition more when available executive control resources are scarce (Hofmann et al, 2008;Salemink & Wiers, 2012 It is not necessarily surprising that interpretive bias effects were only found with social threat items. The participants were students at a small private university; their age and socio-economic status may make social threats more of an everyday concern than the threat of violence or illness (see Helzer et al, 2009;Mathews & MacLeod, 1985). Since we completed the study, informal questioning of some of these students has confirmed that most are much more concerned about 'social death' than they are about actual death, perhaps due to their relatively privileged status in Istanbul society.…”
Section: Discussionmentioning
confidence: 99%
“…This builds on the work of Salemink and Wiers (2012) by showing that a within-participants experimental manipulation of executive control capacity (WM load) moderates trait anxiety's effects on interpretive bias, and supports the hypothesis that latent emotion-related biases influence cognition more when available executive control resources are scarce (Hofmann et al, 2008;Salemink & Wiers, 2012 It is not necessarily surprising that interpretive bias effects were only found with social threat items. The participants were students at a small private university; their age and socio-economic status may make social threats more of an everyday concern than the threat of violence or illness (see Helzer et al, 2009;Mathews & MacLeod, 1985). Since we completed the study, informal questioning of some of these students has confirmed that most are much more concerned about 'social death' than they are about actual death, perhaps due to their relatively privileged status in Istanbul society.…”
Section: Discussionmentioning
confidence: 99%
“…Data extracted could include attentional bias indices, correlations between an anxiety measure and an attentional bias score, or within-group statistics such as t-values. In three cases (Broerena, Murisa, Bouwmeestera, Field, & Voerman, 2011;Helzer, Connor-Smith, & Reed, 2009;Telzer et al, 2008) a beta-weight was reported. This was converted to a correlation coefficient using a formula described by Peterson and Brown (2005), and included in the between-groups analysis.…”
Section: Selection Of Studiesmentioning
confidence: 93%
“…Taghavi et al, 1999) or short (masked) periods (e.g. Helzer, Connor-Smith and Reed, 2009) and in those studies that have attempted to tailor stimulus onset asynchrony (SOA) to childrens' pre-test reading performance (Schippell et al, 2003).…”
Section: Evidence In Child and Adolescent Samplesmentioning
confidence: 99%